You are on page 1of 10

Combinatorics and Graph Theory

Exam - 28 January 2010


Michael Bushell
michael.bushell@student.manchester.ac.uk
December 23, 2012
1
2
(1) (a) (i) A tree is a connected, acyclic graph.
(ii) Let G = (V, E). A subgraph of G is a graph G

= (V

, E

) such
that V

V and E

E. A spanning tree of G is a subgraph


of G which contains all vertices of G and which is also a tree.
(b) See Theorem 1.1 in lecture notes.
(c) Using the method of spanning trees, we have the following spanning
trees containing the edge sa or bc on the path from s to t.
s
a
b
c
t
2
3
2
2
s
a
b
c
t
2
3
2
1
s
a
b
c
t
2
4
2
1
s
a
b
c
t
2
4
2
2
s
a
b
c
t
2
4 3
2
s
a
b
c
t
2
4 3
1
s
a
b
c
t
2
3
2 1
s
a
b
c
t
2
4
2 1
With respective weights 1/24, 1/12, 1/16, 1/32, 1/48, 1/24, 1/12, 1/16.
The edge sa appears in every tree on the path from s to t, so
I
sa
= (1/24+1/12+1/16+1/32+1/48+1/24+1/12+1/16) = 41/96
The edge bc appears positively in the 2
nd
tree and negatively in 4
th
3
tree, so
I
bc
= (1/12 1/32) = 5/96
We are given that I
bc
= 1, hence = 96/5.
Therefore
I
sa
= 41/96 = (41/96)(96/5) = 8.2
4
(2) (a) Given a directed graph G = (V, E), a ow is a function f : E R
such that
(x, y) E : 0 f(x, y) c(x, y), and
x V \{s, t} we have

xyE
f(x, y) =

yxE
f(y, x)
(b) Let (S, T) be a cut of G, then
v(f) =

syE
f(s, y)

ysE
f(y, s)
=

xS
_

xyE
f(x, y)

yxE
f(y, x)
_
Because for all terms except when x = s, the value inside the large
brackets is equal to 0 by the denition of a ow. We can rewrite this
as follows
v(f) =

xS,yV,xyE
f(x, y)

xS,yV,yxE
f(y, x)
For every edge (x, y) such that x, y S, the value +f(x, y) appears
precisely once in the left sum and f(x, y) appears precisely once in
the right sum, cancelling each other.
This just laves the edges (x, y) such that x S, y T, hence
v(f) =

xS,yT,xyE
f(x, y)

xS,yT,yxE
f(y, x)

xS,yT,xyE
f(x, y)

xS,yT,xyE
c(x, y)
= c(S, T)
Therefore, the value of any ow is less than or equal to the capacity
of any cut.
(c) The following ow can be found
5
s
a
c
e
b
d
f
t
9(10)
1(1)
2(2)
9(10)
2(2)
3(3) 4(4) 0(3)
2(2)
1(5) 2(2) 1(2)
2(2)
5(7)
6(10)
by starting from an empty ow, and using the augmenting paths and
increments as follows
path s, a, b, t, increment = 4,
path s, a, b, d, t, increment = 2,
path s, a, b, d, e, f, t, increment = 1,
path s, a, b, c, d, e, f, t, increment = 1,
path s, a, b, c, e, f, t, increment = 1,
path s, c, d, f, t, increment = 1,
path s, e, f, t, increment = 2.
giving a ow of value 12.
We can check by nding the cut (using notation as in the lecture
notes)
S
0
= {s}, S
1
= {s, a}, S
2
= {s, a, b}, S
3
= {s, a, b}
hence
(S, T) = ({s, a, b}, {c, d, e, f, t})
is the required cut whose capacity is
c(S, T) = 1
..
sc
+ 2
..
se
+ 2
..
bc
+ 3
..
bd
+ 4
..
bt
= 12
as expected (edges labelled under their capacities).
(d) See Theorem 2.6 in lecture notes.
6
(3) (a) A sequence {a
n
}

n=0
has ordinary power series generating function
given by the formal power series

n=0
a
n
x
n
.
(b) If f(x) =

n0
a
n
x
n
ops
{a
n
}
n0
, then
f

(x) =

n0
na
n
x
n1
hence, working from the deniton
{na
n
}
n0
ops

n0
na
n
x
n
= x

n0
na
n
x
n1
= xf

(x)
as claimed.
(c) If f(x)
ops
{a
n
}
n0
and g(x)
ops
{b
n
}
n0
, then
f(x)g(x) =
_

n0
a
n
x
n
__

n0
b
n
x
n
_
=

n0
_
n

k=0
a
k
b
nk
_
x
n
ops

_
n

k=0
a
k
b
nk
_
n0
by denition.
(d) Using standard results of geometric series
{1}
n0
ops

n0
x
n
=
1
1 x
then by applying (b) twice
{n}
n0
ops
x
d
dx
_
1
1 x
_
=
x
(1 x)
2
{n
2
}
n0
ops
x
d
dx
_
x
(1 x)
2
_
=
x(1 + x)
(1 x)
3
7
so by denition
{n
2
n + 1}
n0
ops

n0
(n
2
n + 1)x
n
=

n0
n
2
x
n

n0
nx
n
+

n0
x
n
=
1
1 x

x
(1 x)
2
+
x(1 + x)
(1 x)
3
=
1 + 2x 3x
2
(1 x)
3
(e) Write
{a
n
}
n0
ops

n0
a
n
x
n
= A(x)
then
{a
n+k
}
n0
ops

n0
a
n+k
x
n
=
A(x) a
0
a
1
x a
k1
x
k1
x
k
so using this and the recurrence relation gives
A(x) a
0
a
1
x
x
2
= 6
A(x) a
0
x
8A(x)
hence
A(x) =
2x + 1
(1 2x)(1 4x)
=
3
1 4x

2
1 2x
= 3

n0
(4x)
n
2

n0
(2x)
n
=

n0
(3 4
n
2 2
n
)x
n
ops
{3 4
n
2 2
n
}
n0
therefore
a
n
= 3 4
n
2 2
n
since the sequence uniquely determines the generating function.
8
(f) Dene
a
n
= (1)
n
_
2010
n
_
, b
n
=
_
2010 + n
2010
_
for n 0, then
{a
n
}
n0
ops

n0
_
2010
n
_
(1)
n
x
n
=
2010

n=0
_
2010
n
_
(x)
n
=(1 x)
2010
where summation is over 0 n 2010 since the binomial coecients
are 0 for n > 2010, and the nal step follows from the binomial
theorem.
We also have
{b
n
}
n0
ops

n0
_
2010 + n
2010
_
x
n
=
1
(1 x)
2011
using the identity given in the question.
Hence, using the product formula in (c), we have
_
n

k=0
a
k
b
nk
_
ops
(1 x)
2010

1
(1 x)
2011
=
1
1 x
ops
{1}
n0
Therefore, since the sequence uniquely determines the generating
function, we have
1 =
n

k=0
a
k
b
nk
=
n

k=0
(1)
k
_
2010
k
__
2010 + n k
2010
_
as claimed.
9
(4) (a) A sequence {a
n
}

n=0
has exponential generating function given by the
formal power series

n=0
a
n
x
n
/n!.
(b) Write {a
n
}
n0
egf
f(x) =

n0
a
n
x
n
/n!, then
df(x)
dx
=

n1
a
n
x
n1
(n 1)!
=

n0
a
n+1
x
n
n!
egf
{a
n+1
}
n0
and induction on k gives the result
d
k
f(x)
dx
k
egf
{a
n+k
}
n0
as required.
(c) Suppose {a
n
}
n0
egf
f(x) and {b
n
}
n0
egf
g(x), then
f(x)g(x) =
_

n0
a
n
x
n
n!
__

n0
b
n
x
n
n!
_
=

n0
_
n

k=0
a
n
k!
b
nk
(n k)!
_
x
n
=

n0
_
n

k=0
_
n
k
_
a
n
b
nk
_
x
n
n!
egf

_
n

k=0
_
n
k
_
a
n
b
nk
_
n0
as claimed.
(d) Let {a
n
}
n0
egf

n0
a
n
x
n
/n! = A(x), then
{na
n
}
n0
egf

n0
na
n
x
n
n!
=

n0
a
n
x
n
(n 1)!
= xA

(x)
As {1}
n0
egf
e
x
, it follows that
{n}
n0
egf
xe
x
and {n
2
}
n0
egf
x(x + 1)e
x
using (b) and the recurrence relation gives
A

(x) = xA

(x) x(x + 1)e


x
+ 2e
x
10
hence
A

(X) = (2 + x)e
x
and A(x) = (x + 1)e
x
+ c
1
for some constant c
1
, as 1 = a
0
= A(0) = 1 + c
1
we get c
1
= 0, thus
A(x) = xe
x
+ e
x
egf
{n + 1}
n0
therefore
a
n
= n + 1
is the solution.
(e) Suppose {b
n
}
n0
egf
B(x).
Now by the recurrence relation, using part (b) and the product for-
mula from (c) with {a
n
= 1}
n0
egf
e
x
, we have
B

(x) = e
x
B(x)
hence
_
B

(x)
B(x)
dx =
_
e
x
dx
and so
ln |B(x)| = e
x
+ c
1
and B(x) = c
2
e
e
x
for some constant c
2
. As 1 = b
0
= B(0) = c
2
e, we get c
2
= e
1
giving
B(x) = e
e
x
1
as the solution.

You might also like